TARI BALANSE MADAM PADA MASTARAKAT NIAS DI PADANG SUMATERA BARAT: KAJIAN KOMPARASI BENTUK - Novina Yeni Fatrina (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
Balanse Madam dance is traditional dance of Nias Padang society. Balanse Madam dance belongs to social dance with the married dancer. Balanse Madam dance performance is accompanied with western music instrument such as drum set, accordion, violin, guitar, tambourine, drum and tambour. Balanse Madam dance performance in the customary event in 2007, was different from the one in 1994. To raise the phenomenon in a scientific writing, therefore descriptive qualitative research with observation technique, interview by means of analysis interaction and data analysis using analysis interpretation would be used. It is found that there were form changes in the Balanse Madam performance, including unmar- ried dancer, dance accompanied by single-organ and some different term of com- mand from commander. The differences might be used by discontinuous inherit- ance system. Keywords: Balanse Madam, comparation, form.